Formulation and Characterization of Mefenamic Acid Self Nanoemulsifying Drug Delivery System (SNEDDS) Preparations - Farrah Bintang Sabiti; Sukarno (HM Publisher, 2024)
Mefenamic acid is included in BCS (biopharmaceutical classification system) class II, namely high permeability and low solubility. This research aims to obtain a good formula for oleic acid oil, tween 80, and PEG 400 according to the characterization test of emulsification time, % transmittance, drug loading, globule size, and zeta potential. This research was an experimental study by formulating mefenamic acid in the form of SNEDDS which was made 1 formula was made in the form of SNEDDS with the composition of oleic acid, tween 80, and PEG 400 and characterization tests were carried out for emulsification time, % transmittance, drug loading, globule size, zeta potential. The yield of the oleic acid formula is 1%, tween 80 is 8%, and PEG 400 is 1%. The emulsification time characterization test resulted in 17 seconds, % transmittance of 97%, drug loading of 179.81 mg, globular size of 85.8 nm and zeta potential of -1.6 mV.